Material analysis and optical quality assessment of opacified hydrophilic acrylic intraocular lenses after pars plana vitrectomy - Yildirim, Timur Mert; Auffarth, Gerd U.; Łabuz, Grzegorz; Bopp, Silvia; Son, Hyeck Soo; Khoramnia, Ramin (American journal of ophthalmology, 2018)
Explanted hydrophilic intraocular lenses (IOLs) with clinically significant opacification after pars plana vitrectomy (PPV) were assessed for material change and optical quality, in an in vitro laboratory study.
Gesehen am 22.04.2020